PEMBERIAN URIN SAPI PADA BIBIT KARET (Hevea brasiliensis Muell. Arg) STUM MATA TIDUR - Elbi Annas; Elza Zuhry (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
This study aims to determine the provision of cow urine and get the best concentration to support the growth of seedlings of the rubber budded stump. Research conducted at the Experimental station, Faculty of Agriculture, University of Riau, from February to May 2016. This study was conducted experimentally using completely randomized design, which consists of 5 treatments and 3 replications in order to obtain 15 experimental units. The treatments were cow urine concentration as follows: U0 = without cow urine, U1 = concentration of cow urine 5%, U2 = concentration of cow urine 10%, U3 = concentration of cow urine 15%, and U4 = concentration of cow urine 20%. Parameters those observed were seedling height, leaf number, stem diameter and leaf area. Data were analyzed using analysis of variance and Duncan’s multiple range test at 5% level. The result showed that administration of multiple concentration of cow urine can increase the amount of leaf and stem diameter rubber budded stump. Giving cow urine 15% and 20% demonstrated better seedling performance compare to without the provision of cow urine, 5% and 10%. To improve seedling performance of budded stump should use cow urine with concentration of 15%.Keywords : budded stump, rubber seeds, cow urine, the growth of seedlings